MENINGKATKAN KETRAMPILAN MAHASISWA DALAM MENULIS KARANGAN NARASI MELALUI PENGGUNAAN MEDIA GAMBAR SERI (Penelitian Tindakan Kelas Pada Mahasiswa Semester 2 kelas 01 Prodi PBI FKIP UNISRI Tahun Akademik 2013/2014) - Handayani, Sri (Widya Wacana: Jurnal Ilmiah, 2014)
This research is aimed to know whether picture series can improve students' writing skill or not and how is the class condition when it is used to teach narrative. The research was done in English Department, Teacher Training and Education Faculty of Slamet Riyadi University. The subject of the study was the second semester students of English Department Academic Year 2013/2014 consisting of 18 students. It was a classroom action research. The researcher did some steps for each cycle. They were planning, action, observation, and reflection. In collecting the data, the researcher applied several techniques including observation, field notes, interview, questionnaire, and test. To analyze the test, the researcher used descriptive statistics including the average scores and students' score categories. To analyze the qualitative data, the researcher used flow model analysis that draws the conclusions from available data. She observed the students' response in teaching learning process supported by field notes, interview, and questionnaire and finally, she drew the conclusion. In conclusion, picture series is empirically able to improve students' writing skill, it can be shown from the result of Pre Test, Post Test-1 and Post Test-2.The result of Pre-Test is 61,37 , The result of Post Test-1 is 66,60, and the result of Post Test-2 is 73,57 . It means that the students score in writing improves significantly. The class condition becomes more alive and conducive. In short, it is recommended to the lecturer Â to use picture series in teaching writing.